2017
DOI: 10.1007/s10533-017-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme flooding mobilized dissolved organic matter from coastal forested wetlands

Abstract: Two intense rainfalls [Hurricane Joaquin (2015) and Hurricane Matthew (2016)], one year apart, provided a unique opportunity to examine changes in dissolved organic matter (DOM) dynamics in coastal blackwater rivers under extreme flooding conditions in the southeastern United States. Two sites along Waccamaw River (a coastal blackwater river) and the outflow of 18 sub-basins of Yadkin-Pee Dee Basin were sampled during and after the flooding events. The peaks of dissolved organic carbon (DOC) and nitrogen (DON)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…Thus, we posit that as the river became hydrologically connected to adjacent wetlands, mobilization of wetland‐derived DOC into the main channel clearly augmented, if not dominated, any upland sources of DOC. In the Yadkin‐Pee Dee coastal watershed in South Carolina, flow‐separation analysis indicated the drainage of wetlands via subsurface pathways after storm runoff from Matthew had declined and thus extended the shunt of terrigenous, wetland‐derived DOC to coastal waters, similar to what our observations imply (Majidzadeh et al, ). These results, coupled with the long residence time of enclosed coastal waters such as sounds, explain the surprisingly long retention of terrigenous material flushed from the watershed into the NRE‐PS, which persisted in this coastal system well into November and early December roughly 2 months following passage of Hurricane Matthew over the region (Table ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, we posit that as the river became hydrologically connected to adjacent wetlands, mobilization of wetland‐derived DOC into the main channel clearly augmented, if not dominated, any upland sources of DOC. In the Yadkin‐Pee Dee coastal watershed in South Carolina, flow‐separation analysis indicated the drainage of wetlands via subsurface pathways after storm runoff from Matthew had declined and thus extended the shunt of terrigenous, wetland‐derived DOC to coastal waters, similar to what our observations imply (Majidzadeh et al, ). These results, coupled with the long residence time of enclosed coastal waters such as sounds, explain the surprisingly long retention of terrigenous material flushed from the watershed into the NRE‐PS, which persisted in this coastal system well into November and early December roughly 2 months following passage of Hurricane Matthew over the region (Table ).…”
Section: Resultssupporting
confidence: 89%
“…Second, the influence of wetlands on terrigenous DOC in the estuary and sound following Matthew was exemplified by the range of wetland δ 13 C and SUVA 254 values (−29.4 ± 0.7‰ and 4.9 ± 0.5 L·mg C −1 ·m −1 , respectively) in contrast with values for the Neuse River above head of tides at Ft. Barnwell during the same period (−25.9 ± 0.6‰ and 3.6 ± 0.5 L·mg C −1 ·m −1 ). The lower δ 13 C values and higher SUVA 254 values of the wetlands bracketed the majority of NRE-PS values, which strongly suggested the importance of wetland DOC to these coastal waters, similar to many upland watersheds with forested wetlands (Lambert et al, 2015;Majidzadeh et al, 2017).…”
Section: Resultsmentioning
confidence: 72%
“…Our results indicate that due to the hydrologic connectivity of the wetlands upstream of the estuary, around 70-77% of the 32% annual load increase in the NRE can be attributed to the wetlands. Similarly, Majidzadeh et al (2017) indicated that in the Yadkin-Pee Dee Hurricane Matthew exported a large amount of wetland DOC.…”
Section: Shunt: Rapid Delivery Of a Majority Of Doc Coastal Waters Inmentioning
confidence: 99%
“…These results should be interpreted with caution because C E/I was not measured directly, but they are within the range of component rates measured directly from along the Waccamaw River during two separate and overlapping study years. Majidzadeh et al (2017) found that dissolved organic C (DOC) fluxes, which would represent a large portion of C E/I , ranged from 125 g C · m À2 · year À1 in a dry year to 421 g C · m À2 · year À1 in a wet year, or 28%-95% of our average C E/I estimation in a given year. Studies of hydrologic total DOC fluxes through lateral export from coastal estuaries of the eastern United States have documented an average of 46 g C · m À2 · year À1 from the Gulf of Maine estuaries to 168 g C · m À2 · year À1 from the South Atlantic 10.1029/2018GB005897…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 81%